Developmental exposure to indoor flame retardants and hypothalamic molecular signatures: Sex-dependent reprogramming of lipid homeostasis - Kozlova, Elena V.; Denys, Maximillian E.; Benedum, Jonathan; Valdez, Matthew C.; Enriquez, Dave; Bishay, Anthony E.; Chinthirla, Bhuvaneswari D.; Truong, Edward; Krum, Julia M.; DiPatrizio, Nicholas V.; Deol, Poonamjot; Martins-Green, Manuela; et al. (Frontiers in Endocrinology, 2022)
Polybrominated diphenyl ethers (PBDEs) are a class of flame-retardant organohalogen pollutants that act as endocrine/neuroendocrine disrupting chemicals (EDCs). In humans, exposure to brominated flame retardants (BFR) or other environmentally persistent organic pollutants (POPs) such as polychlorinated biphenyls (PCBs) and novel organophosphate flame retardants has been associated with increasing trends of diabetes and metabolic disease. However, the effects of PBDEs on metabolic processes and their associated sex-dependent features are poorly understood. The metabolic-disrupting effects of perinatal exposure to industrial penta-PBDE mixture, DE-71, on male and female progeny of C57BL/6N mouse dams were examined in adulthood. Dams were exposed to environmentally relevant doses of PBDEs daily for 10 weeks (p.o.): 0.1 (L-DE-71) and 0.4 mg/kg/d (H-DE-71) and offspring parameters were compared to vehicle control (VEH/CON). The following lipid metabolism indices were measured: plasma cholesterol, triglycerides, leptin, adiponectin and liver lipids. L-DE-71 female offspring were particularly affected, showing hypercholesterolemia, elevated liver lipids and fasting plasma leptin as compared to same-sex VEH/CON, while L- and H-DE-71 male F1 only showed reduced plasma adiponectin. We found that mean liver lipid content was significantly elevated in L-DE-71 female (but not exposed male) offspring compared to controls. Oil red O staining revealed fatty liver in female offspring and dams. General measures of adiposity, body weight, white and brown adipose tissue (BAT), and lean and fat mass were weighed or measured using EchoMRI. DE-71 did not produce abnormal adiposity, but decreased BAT depots in L-DE-71 females and males relative to same-sex VEH/CON. To begin to address potential central mechanisms of deregulated lipid metabolism, we used RT-qPCR to quantitate expression of hypothalamic genes in energy-regulating circuits that control lipid homeostasis. Both doses of DE-71 sex-dependently downregulated hypothalamic expression of Lepr, Stat3, Mc4r, Agrp, Gshr in female offspring while H-DE-71 downregulated Npy in exposed females relative to VEH/CON. In contrast, exposed male offspring displayed upregulated Stat3 and Mc4r. Intestinal barrier integrity was not affected by DE-71 exposure. These findings indicate that maternal transfer of PBDEs disproportionately endangers female offspring to lipid metabolic reprogramming that may exaggerate risk for adult metabolic disease.